HARTA BENDA DIGITAL SEBAGAI OBJEK WARIS DALAM PERSPEKTIF HUKUM ISLAM DAN URGENSI PERATURAN PERUNDANG UNDANGAN DI INDONESIA - Usman (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
The purpose of the research in this journal article is to explore and analyze the status and mechanism of inheritance of digital assets in the context of Islamic law in Indonesia, with the hope of providing a deeper understanding of the recognition of digital assets as part of inherited property. The research method used includes a legislative approach and conceptual analysis, with data collection through library research to find relevant legal materials, as well as analyzing primary data sources such as the Qur'an and laws. The results show that Islamic inheritance law regulates the process of transferring property from a deceased individual to his heirs, but challenges in applying inheritance law to digital assets still exist, so regulatory adjustments are needed to be in line with technological developments and community needs. Keyword : inheritance, Islamic law, digital property